ANALISIS FRAMING KEBIJAKAN GUBERNUR BALI DALAM PEMBATALAN DRAWING PIALA DUNIA U-20 - Pratyaksa, I Gede Titah; Eka Putri, Ni Luh Wiwik (IAHN Gde Pudja Mataram, 2023)
Football issues, political actors, individuals and parties, the mass media function to convey their political messages to the public in a polite way (because it is through mass media intermediaries). The goal is only one, namely the construction of public opinion which will greatly affect the results of political achievements. The purpose of this study was to find out the news frame for the governor of Bali's policy in canceling the U-20 World Cup draw on www.balipost.com and www.nusabali.com. This research uses a qualitative approach with a case study method at www.balipost.com and www.nusabali.com. Data collection techniques using observation and literature study. This study uses the concept of framing and uses the Pan and Kosciki framing analysis method. The results of the research include, first, framing from the balipost media including the Bali Province PDI Perjuangan Faction (FPDIP) supporting Governor Koster's policy of rejecting the Israeli national team. Furthermore, the second framing from the balipost is that Governor Koster did not reject the FIFA U-20 World Championship, but only conveyed his rejection of the presence of the Israel Team competing in Bali. Meanwhile, framing from the Nusabali media included, firstly, Governor Koster I Wayan Koster did not reject the U-20 World Cup, but only rejected the Israeli National Team. Furthermore, the second framing from Nusabali is that the Governor of Bali, I Wayan Koster, was not wrong in making a decision. This was conveyed by the Chairman of the Hanura Party DPD Bali Province I Kadek Arimbawa or often called Lolak.